Substance P is increased in patients with sickle cell disease and associated with haemolysis and hydroxycarbamide use - Brandow, Amanda M. (Br J Haematol, 2016)
Sickle cell disease (SCD) pain transitions from acute to chronic for unknown reasons. Chronic elevation of the pain neurotransmitter substance P (SP) sensitizes pain nociceptors. We evaluated SP levels in controls and SCD patients during baseline and acute pain and investigated associations between SP and age, gender, pain history, haemolysis and hydroxycarbamide (also termed hydroxyurea) use. Plasma SP levels were measured using enzyme-linked immunosorbent assay. Independent samples t-test compared SP levels between: 1) SCD baseline and controls and 2) SCD baseline and acute pain. Multivariate linear regression determined associations between SP and age, gender, pain history and hydroxycarbamide use. Spearman correlation determined an association between SP and haemolysis. We enrolled 35 African American controls, 25 SCD baseline and 12 SCD pain patients. SCD patients were 7-19 years old. Mean±standard deviation SP level (pg/ml) in SCD baseline was higher than controls (32.4±11.6 vs. 22.9±7.6, P=0.0009). SP in SCD pain was higher than baseline (78.1±43.4 vs. 32.4±11.6, P=0.004). Haemolysis correlated with increased SP: Hb (r=−0.7, P=0.0002), reticulocyte count (r=0.61, P=0.0016), bilirubin (r=0.68, P=0.0216), LDH (r=0.62, P=0.0332), aspartate aminotransferase (r=0.68, P=0.003). Patients taking hydroxycarbamide had increased SP (β=29.2, P=0.007). SP could be a mediator of or marker for pain sensitization in SCD and a biomarker and/or target for novel pain treatment.